2018
DOI: 10.1016/j.applanim.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of negative affective state in Cavalier King Charles Spaniels with syringomyelia

Abstract: Syringomyelia is a common and chronic neurological disorder affecting Cavalier King Charles Spaniels. The condition is putatively painful, but evaluating the affective component of chronic pain in non-human animals is challenging. Here we employed two methods designed to assess animal affect – the judgement bias and reward loss sensitivity tests – to investigate whether Cavalier King Charles Spaniels with syringomyelia (exhibiting a fluid filled cavity (syrinx) in the spinal cord of ≥2mm diameter) were in a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Responses to the ambiguous stimuli in the judgement bias task differed from some other studies. Rather than an intermediate response to the middle bowl (as seen in Cockburn et al 37 and others), dogs showed similar response latencies to NP and MID, with a significant increase in latency to NN. Such response patterns were previously described in Muller et al 76 , and were speculated to be attributable to personality differences.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Responses to the ambiguous stimuli in the judgement bias task differed from some other studies. Rather than an intermediate response to the middle bowl (as seen in Cockburn et al 37 and others), dogs showed similar response latencies to NP and MID, with a significant increase in latency to NN. Such response patterns were previously described in Muller et al 76 , and were speculated to be attributable to personality differences.…”
Section: Discussionsupporting
confidence: 69%
“…This is less likely, given our sample of over 35 dogs for each task (judgement bias n = 37; attention bias, n = 36), which is higher than other comparable studies that detected differences in affective state using the judgement bias paradigm e.g. eight dogs with syringomyelia vs. 13 controls 37 . However, as epilepsy is a heterogenous disease, even within-breed, it is possible that a larger sample is needed.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Some studies in this area, whilst reporting a significant association between emotions and cognitive biases in dogs, have reported methodological and statistical issues, including a small sample size that makes it hard to infer a general behavioural pattern [ 37 , 38 ], the employment of a single ambiguous trial, the outcome of which could be influenced by momentary distraction [ 39 , 40 ] and the use of a statistical approach that evaluates the average dog’s response instead of single trial responses, thereby reducing variability in the data [ 27 , 31 , 41 ]. Averaged measures are inevitably less accurate since, during the test, trials are repeated for each dog and for each type of cue and the number of repetitions is not consistent among cues (more trials for each trained cue, less trials for each ambiguous cue to minimize a potential learning effect).…”
Section: Introductionmentioning
confidence: 99%